2005
DOI: 10.1080/14992020500057731
|View full text |Cite
|
Sign up to set email alerts
|

Screened and unscreened hearing threshold levels for the adult population: Results from the Nord-Trøndelag Hearing Loss Study Niveles de umbrales auditivos tamizados y no tamizados en la población adulta. Resultados del estudio Nord-TrøndeIag sobre hipoacusias

Abstract: This paper presents normative data of hearing threshold levels of a population screened with various criteria, as compared to unscreened population data. Computer-controlled pure-tone audiometry was administered to the adult population in Nord-Trøndelag County, Norway, during 1995-1997. The 51975 participants also provided questionnaire information about occupational and leisure noise exposure, previous ear infections, and head injury. While screening had little effect on the median hearing threshold levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 13 publications
3
41
2
Order By: Relevance
“…We found two Italian studies in two different samples [18, 19], six Swedish studies in three different samples [2025], two Norwegian studies in one sample [26, 27], four Finish studies in three samples [12, 13, 28, 29], two British studies in two samples [30, 31], one study in Sweden, Denmark and Finland with one of the aforementioned Finish samples [32], and a Dutch study [33]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found two Italian studies in two different samples [18, 19], six Swedish studies in three different samples [2025], two Norwegian studies in one sample [26, 27], four Finish studies in three samples [12, 13, 28, 29], two British studies in two samples [30, 31], one study in Sweden, Denmark and Finland with one of the aforementioned Finish samples [32], and a Dutch study [33]. …”
Section: Resultsmentioning
confidence: 99%
“…Some studies either did not separate age and gender [12, 13, 18, 25, 29, 30, 33], did not calculate row and column prevalence for hearing impairments among other impairments [20], did not report sub-sample sizes for age groups [26], had overlapping age class limits [18], or had inconsistent hearing loss criteria between age groups [29]. Three studies did not report prevalence data even though it seemed possible judging from the description of the data [2224, 27]. In the study of Smits et al [33] we derived approximate prevalence rates from a figure.…”
Section: Discussionmentioning
confidence: 99%
“…The standard deviation of the hearing threshold determined by means of the ascending method among the population of young subjects without prior hearing problems, σ pop_asc , can be estimated on the basis of literature data [19]. The distribution of the hearing threshold at 1kHz determined for the population of 2490 subjects was approximated with normal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no significant differences were noted between both groups. The prevalence of notches at 6000 Hz in the control group is not surprising since according to the Nord-Trøndelag Hearing Loss Study [31] such notches were observed both in unscreened and screened for a history of noise exposure and ear-related disorders and diseases populations of men and women up to 40 years old. Moreover, some earlier studies in musicians, including professional orchestral musician, have also shown high frequency notches (mainly at 6000 Hz) in audiograms [7,9,10].…”
Section: Disscusionmentioning
confidence: 99%